2021
DOI: 10.18697/ajfand.104.20950
|View full text |Cite
|
Sign up to set email alerts
|

Use and efficacy of low temperature plasma in foods: promising intervention on aflatoxin control in maize in Kenya – A review

Abstract: Maize (Zea mays var. indentata L.) is the most important food security crop in Kenya and plays an important role in human nutrition. Mycotoxins (MTs) are fungal toxic metabolites which naturally contaminate food and feed. When ingested, inhaled or adsorbed through the skin, even in very small concentrations, are associated with various cancers, retarded growth, suppressed immunity and mutations among other complications. Aflatoxins especially aflatoxin B1, are considered the most lethal in the group of more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Since then, numerous investigations have been completed to evaluate the usage of plasma for microbial deactivation (Basaran et al, 2008). Influence of plasma on diverse microorganisms can be entirely selective, in the sense that it could damage infectious microorganisms devoid of damaging host or it can stimulate different pathways in different organisms (Kamano et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, numerous investigations have been completed to evaluate the usage of plasma for microbial deactivation (Basaran et al, 2008). Influence of plasma on diverse microorganisms can be entirely selective, in the sense that it could damage infectious microorganisms devoid of damaging host or it can stimulate different pathways in different organisms (Kamano et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This being a developing area of research, the mechanism of degradation of mycotoxins by use of plasma technology is not completely realized and adequate literature is unavailable. Nevertheless, more recent studies have revealed that plasma can indeed lower and, in some cases; completely eliminate mycotoxins in different foods (Kamano et al, 2021). The pathways of mycotoxin degradation during CP treatment are unavoidably associated with their molecular geometry, the plasma chemistry nature, and so, the reactive species interaction with toxic compounds (Misra et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation